CHANGES IN THE PARAMETERS OF THROMBODYNAMICS AND BLOOD CLOT CONTRACTION IN PATIENTS WITH RHEUMATOID ARTHRITIS - A. D. Peshkova; T. A. Evdokimova; T. B. Sibgatullin; F. I. Ataullakhanov; R. I. Litvinov (Научно-практическая ревматология)
Autoimmune diseases, including rheumatoid arthritis (RA), are risk factors for thrombotic events. Understanding the pathogenetic role of hemostatic changes in RA can assist in developing measures for prevention, prognosis, early diagnosis, and treatment of immune thromboses. Objective: to investigate the state of platelet and plasma hemostasis in patients with RA, as compared to other laboratory parameters and clinical manifestations of the disease. Subjects and methods. Hemostasis was investigated using two relatively new laboratory tests: thrombodynamics and kinetics of blood clot contraction (BCC). Examinations were made in 60 patients with RA and in 50 apparently healthy individuals of the control group. Results and discussion. In patients with RA, the parameters of thrombodynamics and BCC were found to be significantly different from the normal values. According to thrombodynamics, there was an increase in plasma clot growth rate, size, and density, which indicates chronic hypercoagulation. The rate and completeness of BCC were substantially reduced due to platelet dysfunction in patients with RA compared to healthy individuals. The changes in the parameters of thrombodynamics and BCC correlated with the laboratory signs of systemic inflammation and depended on the radiographic stage of the disease. Conclusion. The results of this investigation confirm that hemostatic disorders are present in RA and indicate the informative value of thrombodynamics and BCC tests as indicators of a pre-thrombotic state, including autoimmune pathology.